Pengembangan LKPD Melalui Model Realistic Mathematic Education Pada Materi Pecahan Siswa Kelas IV Sekolah Dasar - Friska, Sonia Yulia; aulia, Salsa; Nanda, Dodi Widia (Universitas PGRI Madiun, 2022)
This study is driven by a desire to develop LKPD in class IV fractions using Realistic Mathematics Education, in order to increase student interest in learning and improve student learning outcomes in the content being taught. To attain this purpose, efforts must be made to establish LKPD as teaching resources through Realistic Mathematics Education. Research and Development (R&D) is the kind of study, and it follow the ADDIE development model, which has consist several stages (Analyze, Design, Development, Implementation, and Evaluation). The test subjects in this study were fourth grade students. Three validators carried out the assessment instrument: content, construct, and language. As a measure of learning efficacy, fill out the validation instrument sheet, the practicality sheet produced by the practitioner, and its success is assessed from student learning outcomes. The validator value obtained a value of 83 percent in the highly valid category, and the practicality value obtained a value of 91 percent in the very practical category, as a result of the development of LKPD. The results of the effectiveness score obtained a value of 82 percent, indicating that the very practical category is very useful in increasing learning outcomes.